Exposure of pigs to glyphosate affects gene-specific DNA methylation and gene expression. (2022) - Larsen, Knud; Christensen, Thomas Bové; Højberg, Ole; Sørensen, Martin Tang
Abstract: Glyphosate ( N -(phosphonomethyl)glycine) is a broad-spectrum systemic herbicide and crop desiccant. Glyphosate has long been suspected of leading to the development of cancer and of compromising fertility. Herbicides have been increasingly recognized as epigenetic modifiers, and the impact of glyphosate on human and animal health might be mediated by epigenetic modifications. This article presents the results from an animal study where pigs were exposed to glyphosate while feeding. The experimental setup included a control group with no glyphosate added to the feed and two groups of pigs with 20 ppm and 200 ppm of glyphosate added to the feed, respectively. After exposure, the pigs were dissected, and tissues of the small intestine, liver, and kidney were used for DNA methylation and gene expression analyses. No significant change in global DNA methylation was found in the small intestine, kidney, or liver. Methylation status was determined for selected genes involved in various functions such as DNA repair and immune defense. In a CpG island of the promoter for IL18, we observed significantly reduced DNA methylation for certain individual CpG positions. However, this change in DNA methylation had no influence on IL18 mRNA expression. The expression of the DNA methylation enzymes DNMT1, DNMT3A, and DNMT3B was measured in the small intestine, kidney, and liver of pigs exposed to glyphosate. No significant changes in relative gene expression were found for these enzymes following dietary exposure to 20 and 200 ppm glyphosate. In contrast, a significant increase in expression of the enzyme TET3, responsible for demethylation, was observed in kidneys exposed to 200 ppm glyphosate. Graphical Abstract: ga1 Highlights: A large animal study with exposure of pigs to glyphosate is presented here. Pigs were exposed to 20 ppm and 200 ppm in the diet. No significant changes in global DNA methylation was observed. A significantly reduced DNA methylation was found in the porcine IL18 promoter. A significant increase in TET3 expression was seen in porcine kidneys exposed to 200 ppm glyphosate.